ANALYSIS OF VISUAL EFFECTS IN â€œEVERYTHING EVERYWHERE ALL AT ONCEâ€ (2022) : BUILDING A MULTIVERSE NARRATIVE - Aileen Jane (Cinelook: Journal of Film, Television, and New Media, 2025)
To investigate the role of visual effects in facilitating a multiverse story within a movie, the article Analysis of Visual Effects in the Film 'Everything Everywhere All at Once' (2022) in Building the Audience's Imagination through Integration of Multiverse World Narrative is used. The purpose is to examine how visual effects help introduce narrative structure, develop characters, enrich theme and enhance overall audience participation. This will be achieved by using Shilo T. McCleanâ€™s theory about integrating narratives with visuals; this approach will involve closely analyzing scenes where visual effects play crucial roles in filmmaking. The paper asserts that differentiating various universes and amplifying the filmâ€™s narrative coherence and emotional impact are among key functions visual effects perform. In view of this, it was concluded that live-action elements must be smoothly integrated with special effects for complicated storytelling and better empathy between viewers and storylines. Further investigation highlights how digital storytelling has made it possible for contemporary films to use visual effects as transformative tools within cinematic works.